Keratitis-Ichthyosis-Deafness Syndrome, Atypical Connexin GJB2 Gene Mutation, and Peripheral T-Cell Lymphoma: More Than a Random Association? - Claudio Fozza; Fausto Poddie; Salvatore Contini; Antonio Galleu; Francesca Cottoni; Maurizio Longinotti; Francesco Cucca (Case Reports in Hematology)
Keratitis-ichthyosis-deafness (KID) syndrome is a rare congenital disorder characterized by skin lesions, neurosensorial hypoacusia, and keratitis, usually due to the c.148G→A mutation involving the connexin 26 gene. We report on a KID patient who showed the atypical c.101T→C mutation and developed a T-cell lymphoma so far never described in this group of patients.